ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN RESUME MEDIS – LITERATURE REVIEW - Nafa Maharani; Atma Deharja; Rossalina Adi Wijayanti; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2022)
A Medical resume is a summary of the whole medical patient's treatment. The incomplete medical resume can cause the patient's medical history to not continue with the patient's previous data. The various factors cause an incomplete medical resume. The research aimed to analyze the aspects related to the completeness of a medical resume. The study is a literature review with database from Google Scholar and Garuda. This research's keywords are factors related AND completeness OR complete AND medical resume OR medical resume OR discharge summary OR discharge summary. The manpower elements are 21,4 percent of good knowledge, 28,5 percent of long working tenure, 21,4 percent of civil servant employment status, 7,1 percent of good attitude, and 7,1 percent of higher education. The motivation elements are 14,2 percent of adequate supervision (monitoring and evaluation), 7,1 percent of good leadership, and 7,1 percent of reward and punishment. Media elements are 7,1 percent of how to pay for BPJS patients and 7,1 percent of directly related work conditions (unique table and chair to fill medical records) and other work environments (lighting and noise room to fill medical resumes). The main factor related to medical resume's completeness is tenure, and other high factors are knowledge and employment status. The writer suggests that health facilities should facilitate patient data completeness, especially for doctors with a new term, bad experience, and non civil servant employment status.